Fabrication, structural and electrical properties of piezoelectric ceramicpolymer lead free nanocomposites / Rahman Ismael Mahdi - Rahman Ismael , Mahdi (2017)
Polyvinylidene Fluoride (PVDF) is one of the few piezoelectrically active semicrystalline polymer materials, but its electrical properties are less potent than most piezoelectric ceramics. However, these properties are improved by copolymers like trifluoroethylene (TrFE) and tetrafluoroethylene (TFE) through improvement of polymer crystallinity. Further improvements can be made by producing polymer-ceramic composite material with highly piezoelectric ceramics. Piezoelectric ceramic materials are excellent candidates for use in solid state applications like transducers and microelectrical- mechanical devices. However, due to their high stiffness and substantial fabrication cost, piezoelectric ceramics cannot be used in many applications. This justifies the extensive research focused on piezoelectric polymers. Piezoelectric polymers are very flexible, easy to fabricate, and have acoustic impedance comparable to soft human tissue. Ultimately, a material with the mechanical properties of a polymer and the piezoelectric properties of a ceramic would be ideal for many piezoelectric applications. Given these considerations, this study aims to develop the processing science necessary to create a lead free nanocomposite and to characterise this nanocomposite. This work consists of three parts. The first and second part focused on optimization of electrical properties of both P(VDF-TrFE) copolymer and BNT-BKT-BT lead-free ceramic. The results suggested that high electrical properties of P(VDF-TrFE) can be obtained at a high degree of crystallinity β- phase, which was attained through material annealing at a temperature close to the Curie temperature. By contrast, the BNT-BKT-BT ceramic showed high electrical properties near Morphotropic Phase Boundary (MPB) and the samples sintered at 1180 ℃ manifested the highest density. As the sintering temperature increased even more, the sample density deteriorated and the second phase was formed. The third part of this work, involved preparation with multiple volume fractions (Ø = 0 -0.30) of thin films of a ferroelectric polymer matrix made of P(VDF-TrFE) copolymer incorporated with a ferroelectric inclusion, BNT. This significantly improved the pyroelectric and ferroelectric responses. A maximum peak of pyroelectric coefficient, p, and remnant polarisation Pr of nearly 50 μC/m2 K and 11.5 μC/cm2, respectively, were obtained for Ø = 0.20. Copolymer incorporation of BNT-based trinary system led to further enhancement. The nanocomposite pyroelectric coefficient and remanent polarization were significantly improved to 90 μC/m2K and 13 μC/cm2, respectively. The contribution from each phase in piezoelectric and pyroelectric was estimated. The nanocomposite was divided into ceramic phase poled only, both phases poled in the same direction, and both phases poled in the opposite direction. When both phases polarised in the same direction, the pyroelectric effects of each phase tended to reinforce each other. Conversely, the piezoelectric effects in this sample tended to cancel out, due to the opposite signs of the piezoelectric coefficient of each phase. Meanwhile, when the phases polarised in opposite direction, piezoelectric activates were improved and d33 increased from 28 to 40 pC/N, with a change in ceramic volume fraction of 0 to 30 %. This behaviour, alongside separate matrix and filler polarisation, could enable development of piezoelectric materials with internal compensation of pyroelectricity or vice versa. Enhanced pyroelectric composites with both phases poled in the same direction could be used in pyroelectric sensors, while composites with phases poled in opposite direction could be used in ultrasonic transducers.